2003
DOI: 10.1046/j.1469-1809.2003.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Y Chromosome and Mitochondrial DNA Characterization of Pasiegos, a Human Isolate from Cantabria (Spain)

Abstract: SummaryMitochondrial DNA sequences and Y chromosome haplotypes were characterized in Pasiegos, a human isolate from Cantabria, and compared with those of other Cantabrian and neighbouring Northern Spain populations. Cantabria appears to be a genetically heterogeneous community. Whereas Lebaniegos do not differ from their eastern Basque and western Asturian and Galician neighbours, Pasiegos and other non-Lebaniego Cantabrians show significant differences with all of them. Pasiegos are peculiar for their high fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
1
45
1
3
Order By: Relevance
“…It has been previously suggested that the Pasiegos are a complex human isolate. On the basis of their high frequency for the North-African Y-chromosome E-M81 haplogroup and a relative abundance of other Y-chromosome and mtDNA haplogroups, of typical northern European ascription, dual gene-flow influences were assumed to affect this isolate (Maca-Meyer et al, 2003). In this study, again, the high frequency of H4 and the absence of H3 resembles the haplogroup H profile found for Moroccan Berbers (Ennafaa et al, 2009).…”
Section: Phylogeography Of H Subhaplogroups In the Cantabrian Cornicementioning
confidence: 50%
See 2 more Smart Citations
“…It has been previously suggested that the Pasiegos are a complex human isolate. On the basis of their high frequency for the North-African Y-chromosome E-M81 haplogroup and a relative abundance of other Y-chromosome and mtDNA haplogroups, of typical northern European ascription, dual gene-flow influences were assumed to affect this isolate (Maca-Meyer et al, 2003). In this study, again, the high frequency of H4 and the absence of H3 resembles the haplogroup H profile found for Moroccan Berbers (Ennafaa et al, 2009).…”
Section: Phylogeography Of H Subhaplogroups In the Cantabrian Cornicementioning
confidence: 50%
“…However, this should now be considered as due to sampling errors because when sample sizes were increased in posterior analyses, V frequencies in the Basque Country dropped to 12.4% (Torroni et al, 2001) and 10.2% (Maca-Meyer et al, 2003). In this study, haplogroup V frequencies in the Cornice are at their peak in Cantabria (19%), dropping westwards to 5.6% in Asturias and to 3.8% in Galicia.…”
Section: Phylogeography and Genetic Diversities Of Hv* And V Haplogromentioning
confidence: 70%
See 1 more Smart Citation
“…The latter is the most widespread haplogroup of the E cluster in Iberia, reaching its highest frequencies both in southern and northern parts of the Iberian Peninsula. 9,26 Relationships among the Basque samples To explore the hypothesis that the Basques might not constitute a homogeneous population, 27,28 we tested the pairwise F ST values among the individual Basque samples. For the binary markers, after Bonferroni correction (a ¼ 0.008), the hypothesis of a single Basque population is rejected (Supplementary Information 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that both continental and Island populations have suffered from North African influences at different levels. [17][18][19][20][21] The Canary Islanders, the populations from Castilla and the southern Spanish populations from Andalusia have been reported to have the highest percentage of North African influences in Spain. 19,20 In order to meet power requirements (see Materials and methods) while preserving the homogeneity of the population, we included 179 unrelated patients, which met severe sepsis criteria, 22 from different Spanish localities with as similar as possible genetic backgrounds: Tenerife, one of the major islands of the Canarian Archipelago (a total of 64 patients) and different localities from Castilla (a total of 115 patients).…”
Section: Patients and Clinical Phenotypementioning
confidence: 99%